2019
DOI: 10.1186/s12889-019-6879-x
|View full text |Cite
|
Sign up to set email alerts
|

Health conditions and occupational risks in a novel group: waste pickers in the largest open garbage dump in Latin America

Abstract: Background The inadequate management of solid waste impacts populations’ health and quality of life, and disproportionately affects developing countries. This study aims to describe a protocol for epidemiological diagnosis, the purpose being to estimate the prevalence of chronic and communicable and non communicable diseases in waste pickers, and the occupational and environmental risk factors to which these are exposed. Methods This is a cross-sectional study, based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
71
1
20

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(92 citation statements)
references
References 29 publications
0
71
1
20
Order By: Relevance
“…A study from India also reported an association between SRH and chronic disease [40]. Chronic diseases like diabetes and hypertension were significantly associated with reporting poor health and were the most prevalent among waste pickers [12,41]. Landfill sites contain chemicals which might have adverse effects on the environment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study from India also reported an association between SRH and chronic disease [40]. Chronic diseases like diabetes and hypertension were significantly associated with reporting poor health and were the most prevalent among waste pickers [12,41]. Landfill sites contain chemicals which might have adverse effects on the environment.…”
Section: Discussionmentioning
confidence: 99%
“…Waste pickers have a higher risk of acquiring a number of diseases and injuries compared to the general population. This is because of exposure to cuts (lesions to the skin) and toxic substances like chemicals, bacteria, dust inhalation, and medical wastes [9][10][11][12]. Diseases they most commonly face include respiratory infections, skin diseases, mental illness, and chronic diseases [11,13].…”
Section: Introductionmentioning
confidence: 99%
“…In a study conducted in India which compared non-waste recyclers to waste recyclers, waste recyclers were found to have significantly higher injuries (75%), respiratory illness (28%), eye infection (29%), and stomach problems (32%), compared to the comparison group (17%, 15%, 18%, and 19% respectively) [10]. Furthermore, a study in Brazil looking at waste recyclers showed a high prevalence of commonly reported diseases such as muscular disorders (78.7%); arboviruses (28.6%); episodic diarrhea (24.9%); hypertension (24.2%); bronchitis (14.3%); intestinal worms (12.6%) and diabetes (10.1%) [11]. The impact of poor health outcomes in informal waste recyclers and the inability to contribute to removal of environmental waste could result in increased spread of diseases in the general population.…”
Section: Introductionmentioning
confidence: 99%
“…The intensity and type of risks depend on where they work (recycling centers, warehouses, on the streets or in garbage dumps), on their working conditions (informal or organized groups), on the nature of the waste (composition, components and decomposition), and the duration of their exposure [5] , [6] . A study in Latin America in 2018 pointed out that the most common reported diseases among waste collectors were osteomuscular disorders (78.7%), arboviruses (28.6%), episodic diarrhea (24.9%), hypertension (24.2%), bronchitis (14.3%), intestinal worms (12.6%) and diabetes (10.1%) [7] . Lucia Botti et al also found that the waste collectors are affected by low ergonomic conditions and highly risk of musculoskeletal disorders [8] .…”
Section: Introductionmentioning
confidence: 99%